Infection of human uterine fibroblasts by Zika virus in vitro: implications for viral transmission in women. (October 2016) - Chen, Joseph C.; Wang, Zuguang; Huang, Hong; Weitz, Sara H.; Wang, Aprilgate; Qiu, Xiaolei; Baumeister, Mark A.; Uzgiris, Arejas
Highlights: Human uterine fibroblasts are susceptible to Zika virus infection. Both African and Puerto Rican Zika strains can infect human uterine fibroblasts. A quantitative reverse transcription PCR with primers targeting the envelop regions of the virus was utilized. Uterine fibroblasts continually produced virus, while maintaining cellular viability over 5 days. Uterine fibroblasts may be linked with heterosexual transmission of Zika virus in women.